Artificially regulated synthesis of nanocrystals in live cells. Issue 6 (9th September 2021) - Liu, An-An; Sun, En-Ze; Wang, Zhi-Gang; Liu, Shu-Lin; Pang, Dai-Wen
Abstract: Live cells, as reservoirs of biochemical reactions, can serve as amazing integrated chemical plants where precursor formation, nucleation and growth of nanocrystals, and functional assembly, can be carried out accurately following an artificial program. It is crucial but challenging to deliberately direct intracellular pathways to synthesize desired nanocrystals that cannot be produced naturally in cells, because the relevant reactions exist in different spatiotemporal dimensions and will never encounter each other spontaneously. This article summarizes the progress in the introduction of inorganic functional nanocrystals into live cells via the 'artificially regulated space–time-coupled live-cell synthesis' strategy. We also describe ingenious bio-applications of nanocrystal–cell systems, and quasi-biosynthesis strategies expanded from live-cell synthesis. Artificially regulated live-cell synthesis—which involves the interdisciplinary application of biology, chemistry, nanoscience and medicine—will enable researchers to better exploit the unanticipated potentialities of live cells and open up new directions in synthetic biology. Abstract : A strategy of 'artificially regulated space–time-coupled synthesis' enables live cells to intracellularly synthesize functional inorganic nanocrystals, opening a new window for synthetic biology.